Evaluation of polymorphonuclear leukocyte elastase levels in neonatal sepsis - Pessar, Shaimaa Abdelmalik (International Journal of Research in Medical Sciences, 2016)
Background: Sepsis is an important cause of neonatal morbidity and mortality. In Egypt, A multi-center study reported that 45.9% of the neonates admitted to neonatal intensive care units (NICUs) were due to suspected neonatal sepsis. Proper management is not guaranteed due to nonspecific symptoms and signs especially at the onset of disease, delay of culture results and high rate of false negative results. Attempts have been made to use hematologic parameters, acute phase reactants and cytokine profiles for early and accurate diagnosis of neonatal sepsis; however, none was adequately sensitive or specific. Polymorphonuclear elastase (PMN-E) is a serine protease secreted during inflammatory diseases. The aim of the current study was to explore the reliability of PMN-E level for the diagnosis of neonatal sepsis and assess response to treatment in comparison to hematological parameters and C - reactive protein (CRP). Methods: The study comprised 30 neonates with proven sepsis, 30 neonates as control group. Both groups were subjected to calculation of hematologic sepsis score (HSS), CRP measurement, blood culture and serum PMN-E levels, the latter was measured both at diagnosis and 6 days after treatment in sepsis group. Results: Serum PMN-E levels were significantly higher in sepsis group (118.4±21.8) than in control group (57.9±27.9) and the best cut-off value was at 85 ng/ml with 97% sensitivity and 81% specificity, PMN-E levels also decreased significantly with response to treatment. Conclusions: Raised PMN-E level was found to be a diagnostic and prognostic marker in neonates with sepsis comparable with CRP and HSS.